Epi-microRNA mediated metabolic reprogramming counteracts hypoxia to preserve affinity maturation - Rinako Nakagawa; Miriam Llorian; Sunita Varsani-Brown; Probir Chakravarty; Jeannie M. Camarillo; David Barry; Roger George; Neil P. Blackledge; Graham Duddy; Neil L. Kelleher; Robert J. Klose; Martin Turner; et al. (Nature Communications)
Abstract To increase antibody affinity against pathogens, positively selected GC-B cells initiate cell division in the light zone (LZ) of germinal centers (GCs). Among these, higher-affinity clones migrate to the dark zone (DZ) and vigorously proliferate by utilizing energy provided by oxidative phosphorylation (OXPHOS). However, it remains unknown how positively selected GC-B cells adapt their metabolism for cell division in the glycolysis-dominant, cell cycle arrest-inducing, hypoxic LZ microenvironment. Here, we show that microRNA (miR)−155 mediates metabolic reprogramming during positive selection to protect high-affinity clones. Mechanistically, miR-155 regulates H3K36me2 levels in hypoxic conditions by directly repressing the histone lysine demethylase, Kdm2a, whose expression increases in response to hypoxia. The miR-155-Kdm2a interaction is crucial for enhancing OXPHOS through optimizing the expression of vital nuclear mitochondrial genes under hypoxia, thereby preventing excessive production of reactive oxygen species and subsequent apoptosis. Thus, miR-155-mediated epigenetic regulation promotes mitochondrial fitness in high-affinity GC-B cells, ensuring their expansion and consequently affinity maturation.